Students' Preferences for Digital Teaching Materials in German Language Learning - Kurnia, Amanda Putri; Dhania Febriane; Jihaan Aprilianah (Nexus Publishing NXP, 2025)
This study aims to identify students’ preferences toward digital learning materials in German language instruction and to explore the factors influencing their effectiveness. A descriptive quantitative approach was employed using a survey method. Data were collected through a questionnaire completed by 40 students from the German Language Education program who had previously used various types of digital learning materials in their coursework. The results indicate that the majority of students regularly use digital materials and exhibit positive preferences toward content that is visually appealing, interactive, easy to understand, and aligned with their language proficiency levels. The most frequently used materials include educational websites and instructional videos, while technologies based on Augmented Reality (AR) and Virtual Reality (VR) remain rarely utilized. Challenges identified include unstable internet connections, limited opportunities for practicing speaking and writing skills, and insufficient classification of materials by proficiency level. Students’ preferences and experiences suggest that digital learning materials that are adaptive, contextual, and support all four language skills are more favored and perceived as effective in the learning process.